Analisis Bibliometrik:Keterkaitan antara Triple Helix dan Open Innovation - Rohmat Hidayatuloh; Tatang Akhmad Taufik (Owner : Riset dan Jurnal Akuntansi, 2023)
This research examines the correlation between Triple Helix and Open Innovation. The study aims to determine: (1) the development of the number of international publications related to Triple Helix and Open Innovation from 2003 to 2023; (2) the mapping of topics related to Triple Helix and Open Innovation based on co-word analysis; (3) the collaboration among authors or researchers related to Triple Helix and Open Innovation. Data collection was done by retrieving publication data from Google Scholar using the "publish or perish" approach with the keywords Triple Helix and Open Innovation within the period of 2003-2023. The data were in RIS/Refman format and analyzed using VosViewer software. The results show that the highest growth of publications related to Triple Helix and Open Innovation from 2003 to 2023 occurred in 2018, with 93 publications or 9.31%. The research findings indicate that the topics related to Triple Helix and Open Innovation from 2003 to 2023 can be divided into six clusters. Based on co-occurrence analysis through network visualization and density visualization, it can be concluded that Triple Helix and Open Innovation are interconnected and have been extensively published. For future research, the authors suggest conducting bibliometric analysis on reputable journal databases or those indexed in Scopus that explore the correlation between Triple Helix and Open Innovation. Additionally, it is necessary to conduct practical approaches such as case studies on the correlation between Triple Helix and Open Innovation within the innovation ecosystem in Indonesia